Чому Україна не інноваційна держава: інституційний аналіз - Дементьєв, В.В.; Вишневський, В.П. (Економічна теорія, 2011)
Розглянуто інституційні перешкоди інноваційної діяльності в Україні. Показано, що основним джерелом прибутку тут є штучне заниження витрат ведення бізнесу за допомоги здійснення економічної влади; наслідком цього стають високі трансакційні витрати інноваційної діяльності, кадровий опір інноваціям, руйнування освітньої та наукової інфраструктури. Institutional impediments to the innovation activities in Ukraine are studied. It is demonstrated that the main source of income in this country is artificial diminishing of the costs of doing business performed through the execution of the economic power. As a result thereof transaction costs for innovations become high, the innovations are confronted bureaucratically and education and science infrastructure falls apart.